Clothing and textile sustainability : current state of environmental challenges and the ways forward - Patwary, Sarif (Array, 2020)
The global clothing and textile industry is facing immense criticism due to its enormous environmental pollution. While demonstrating a slow adoption, brands, retailers, and manufacturers are recognizing the unsustainable nature of the industry. Consumers, too, are also becoming more aware of the environmental issues of the industry. Policymakers are coming up with relevant regulations to set the industry into a sustainable direction. However, the plethora of information, ideas, suggestions, and strategies make it difficult to get a holistic idea of the environmental sustainability challenges that the industry is facing and the necessary actions it should take. This paper reviews the current state of environmental challenges, and the required actions articulated in the literature as related to the clothing and textile industry. Based on this review, suggestions are made for the key stakeholders of the clothing supply chain, and the profile of an environmentally sustainable clothing item is examined. The review revisits the complexity of the clothing supply chain and stresses the urgency of expediting actions.